PENGARUH PRODUK TERHADAP KEPUTUSAN PEMBELIAN KAIN TENUN IKAT SIKKA - Nur Chotimah; Regina Edita; Muhammad Syahrun (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
Everyone has different personal characteristics that will influence their behavior to make purchasing decisions. In improving consumer purchasing decisions, producers should produce products that can meet the needs and desires of consumers. This study aims to determine the effect of the product on the purchase decision of Sikka ikat woven fabric. This research was conducted at Alok market of Maumere in 2021. The population in this study were all consumers who had bought Sikka ikat woven fabric with a total sample of 96 people and used a random sampling technique. The data analysis technique used simple linear regression analysis. Testing data using validity test, reliability test, normality test, and coefficient of determination test using SPSS version 25. The results showed the product had a positive and significant effect on purchasing decisions for Sikka ikat woven fabric by 45.2% and the remaining 54.8% was influenced by other factors that were not investigated in this study. Keyword: products, purchase decision, ikat woven fabric